Modification Of Aggregate Grading For Porous Asphalt. - Hamzah, M O; Samat, M M; K, h Joon; Muniandy, R (2004)

(untitled)
In the 1970’s, the fatality index on Malaysian roads exceeded 20. In 1991, a Cabinet Committee on Road Safety was set up to come up with measures to reduce the predicted number of deaths by 30% or translated into a fatality index of 3.14 by the turn of the century. Among the measures suggested included the application of porous asphalt.